Monitoring Mean Arterial Preasur (MAP) in Traumatic Brain Injury Patients during The Initial 60 Minutes of Manitol 20% - Sandi Alfa Wiga Arsa; Anita Rahmawati; Thatit Nurmawati; Heni Rohmawati (Journal of Ners and Midwifery, 2023)
The effect of manitol 20% on changes in blood pressure after traumatic brain injury is unknown. The purpose of this study was to analyze the differences in blood pressure before and after the administration of 20% mannitol in traumatic brain injury patients at the Intensive Care Unit. This study is a quasi experimental research which uses a pre-post test without control one group design, a method used in observational analytic techniques. The population of this study were all traumatic brain injury patients who were given a manitol infusion of 20% 100ml, with consecutive sampling technique, obtained 12 samples. With a significance threshold of p 0.05, the test was performed using the Paired T test on systolic and MAP data and the post hoc Wilcoxon test on diastolic data.Â Â  paired t-test systolic p=0.000, MAP p=0,000. Wilcoxon test diastolic p=0,002. Decreasing blood pressure 15 minutes after administration of 20% mannitol occurs because half live mannitol which lowers blood pressure and responds to decreased blood pressure autoregulation, at 30 minutes resulting in decreased intra-cranial pressure, improves cerebral perfusion and brain autoregulation that affects systemic blood pressure 60 changes in blood pressure may be due to diuresis effects. During the administration of mannitol there is a change in blood pressure that needs to be monitored